Dynamic model for price of wheat in Bangladesh - Rabbani, Golam; Haque, A. K. M. Ahasanul; Khalek, Abdul (EuroJournals Publishing, Inc., 2009)
Wheat is the second staple food of Bangladesh. In this paper we constructed a dynamic model for wheat price. Basically we constructed a single equation autoregressive integrated moving average (ARIMA) model of the price (quarterly wholesale wheat price). Standard ARIMA analysis rests on the simplifying assumption that the time series is stationary. So, at first stationary of the series is checked. An ARIMA (1,1,0) (2,1,1)4 model is constructed based on the autocorrelation and partial autocorrelation functions. Finally, forecasts are made based on the model developed.